Herbert Daniel & Richard Parker (eds.): Sexuality, Politics and AIDS in Brazil. In Another World? - Godtfredsen, Ulla (Tidsskriftet Antropologi, 1996)
Sexuality, Politics and AIDS in Brazil. In Another World? Anmeldes af Ulla Godtfredsen